Careful use of 16S rRNA gene sequence similarity values for the identification of Mycobacterium species. (March 2018) - Beye, M.; Fahsi, N.; Raoult, D.; Fournier, P.-E.
Abstract: In order to evaluate the suitability of 16S rRNA nucleotide sequence similarity for the classification of new Mycobacterium isolates at the species level, we systematically studied the pairwise identity values of this gene for 131 Mycobacterium species with standing in nomenclature. Only one of the studied species, M. poriferae (0.76%), strictly respected the 95% and 98.65% threshold values currently recommended to determine the affiliation of bacterial isolates to an existing or new genus or species, respectively. All other species exhibited at least an identity value >98.65% and/or <95% with another Mycobacterium species. Therefore, we suggest that interpretation of interspecies 16S rRNA identity values should be made cautiously when classifying a new mycobacterial isolate at the species level.